Between Polygyny and Monogamy: Marriage in Saudi Arabia and Beyond - Sumanto Al Qurtuby (Al-Jami'ah Research Centre, 2022)
Saudi Arabia has long been portrayed as a “hub of polygyny,” a practice of marriage in which a man marries several women simultaneously. However, my recent research among Saudi male youths suggest that this practice is waning nowadays. A younger generation in the Kingdom seems to prefer monogamy—a man marrying one wife—to polygamy for several essential reasons, factors and arguments. Based on interviews and conversations with a number of young Saudis as well as outcomes of survey findings, this article tries to debunk the myth of polygyny in the Kingdom and attempts to understand the rationales and logics behind monogamy choice among male (and female) youths of contemporary Saudi Arabia. The article also briefly highlights the practice of polygyny and monogamy in multiple societies outside Saudi Arabia to compare and gain knowledge on various practices of marriage. Seen from another viewpoint, the article is a reflection of a modern-day fruitful socio-cultural development and change in Saudi Arabia that have received enthusiastic and public acclaim across the globe.Arab Saudi digambarkan sejak lama sebagai ‘pusat poligini’, sebuah praktik pernikahan satu laki-laki dengan sejumlah perempuan secara simultan. Namun dalam penelitian saya terbaru terhadap sejumlah laki-laki muda Arab menyatakan praktik poligini mulai memudar saat ini. Generasi muda di wilayah kerajaan Arab tampaknya mulai memilih monogami, daripada poligami, dengan beberapa alasan, faktor dan argumen yang mendasar. Berdasarkan wawancara dan percakapan dengan sejumlah pemuda Arab yang temuannya menunjukkan, seperti dalam artikel ini adalah menyanggah mitos poligini di kerajaan Saudi dan usaha memahami rasionalitas dan logika monogami pemuda dan pemudi di Arab Saudi dewasa ini. Artikel ini juga sekilas membahas praktik poligini dan monogami di luar Arab Saudi sebagai perbandingan dan pengetahuan mengenai ragam bentuk praktik pernikahan di berbagai masyarakat. Dengan sudut pandang lain, artikel ini mencerminkan kehidupan modern dari aneka perkembangan sosial budaya dan perubahan di Arab Saudi yang menerima semangat dan penerimaan publik lintas dunia.